PENGARUH SISTEM PENGENDALIAN INTERNAL DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA MANAJERIAL DI PERUMDA TIRTA HIDAYAH KOTA BENGKULU - Putri, Marliya Eka; Onsardi, Onsardi; Wahyudi, Dedy (UM. Bengkulu, 2024)
Manager participation in budget preparation and clarity of budget targets can influence performance with an effective internal control system. Research objectives (1) to determine the effect of the internal control system on managerial performance (2) to determine the effect of clarity of budget targets on managerial performance, (3) to determine the effect of the internal control system and clarity of budget targets on managerial performance. The research was carried out at Perumda Tirta Hidayah, Bengkulu City. Respondents were all 47 managerial people. Data collection used a Google Form questionnaire, shared online via WhatsApp messages. Data analysis uses multiple linear regression models and is processed with SPSS software. The results of the research that has been carried out show that partially the internal control system variables have a positive effect on the managerial performance of Perumda Tirta Hidayah, Bengkulu City. Partially, clarity of budget targets has a positive effect on the managerial performance of Perumda Tirta Hidayah, Bengkulu City. Simultaneously, the variables of the internal control system and clarity of budget targets have a positive effect on the managerial performance of Perumda Tirta Hidayah, Bengkulu City Keywords: Internal Control System, Clarity of Budget Targets, Managerial Performance